Sepsis – infection related life-threatening organ dysfunction - Vosylius, Saulius; Nekrašienė, Milda (Lietuvos chirurgija, 2018)
[full article and abstract in Lithuanian; abstract in English]Sepsis is associated with poor outcome of infection especially if not recognized early and not treated promptly. Early confirmed diagnosis, timely and adequate treatment is essential in order to overcome sepsis. Novel medical studies have clarified the pathophysiology of sepsis, but clinicians and researchers still struggle to define diagnostic criteria of sepsis while searching for simple and more specific criteria. The Third International Consensus Definitions for Sepsis and Septic Shock was published in 2016; the main difference from the previous definition is shifting focus to early recognition of organ dysfunction caused by infection. By agreement of experts it is advised to abandon terms of systemic inflammatory response syndrome and severe sepsis. Local infection may lead to sepsis when dysregulated host response to local infection causes organ dysfunction. Septic shock is defined as sepsis-induced hypotension persisting despite adequate fluid resuscitation and requiring use of vasopressors to maintain optimal mean blood pressure as well as confirming hyperlactatemia. The renewed diagnostic criteria of sepsis proposed by physicians and researchers from different specialities is a step forward in promoting new epidemiological and clinical studies, initiatives for better identifying and treating sepsis.
Keywords: sepsis, septic shock, organ failure, diagnosis